PEMANFAATAN CITRA PENGINDERAAN JAUH MULTI TEMPORAL UNTUK KAJIAN TINGKAT BAHAYA EROSI (Kasus di Sub DAS Karang Mumus, Kalimantan Timur) - , M. ADI FATMARAGA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives of the study are inventoring land use changing and erossion potential rate, and also dominant factors affecting erossion analysis in Sub-watershed Karang Mumus multi-temporally. Land cover data was obtained from Landsat TM and ETM+ Image extraction by year, 1997 to 2009. The methods that have tested by interpretation test, so that get the amount of area of land use and its changing using two dimensional matrix for every period (year). On a multi-temporal erossion potential rate analysis, there was calculation through USLE method with several variables, there are erosivity derived from rainfall data, erodibility obtained from land type data, slope and its length obtained from DEM data processing, extracted from SRTM imagery, crop management and soil and conservation obtained from land use data from multi-temporal Landsat imagery. Variables were compiled by statistical analysis with regresion equations and correlation. The result of the study shows that land interpretation test for the year 1997 is 80%, year 2006 is 85%, year 2009 is 77.5%